Elizabethkingia species sepsis after lung transplantation: case report and literature review. Issue 6 (14th October 2013) - Ramanan, P.; Razonable, R.R.
Abstract Elizabethkingia species are environmental bacteria that rarely cause infection in neonates and immunocompromised adults, usually as part of nosocomial outbreaks. We report an isolated fatal case of disseminated Elizabethkingia species infection in a lung transplant recipient and review the literature of this bacterial infection in transplant recipients.